2013
DOI: 10.1007/s13277-013-0732-0
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase 1 is overexpressed in renal cancer and participates in the proliferation and invasion of renal cancer cells

Abstract: Polo-like kinase 1 (Plk1) is an interesting molecule both as a biomarker and as a target for highly specific cancer therapy for several reasons. However, the functional significance of Plk1 in renal cell carcinoma (RCC) has not been reported. To explore whether Plk1 plays a general role in renal carcinoma, we examined the expression of Plk1 protein in renal urothelial carcinoma and cell lines, and analyzed the relationship between Plk1 protein expression and development, proliferation, and invasion of renal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…the 769-P and ACHN cells transfected with PLK1 siRNA demonstrated an increased percentage of cells in the G2/M phase, which supports the findings of previous studies (8,9). A previous study reported that PLK1 was important for the proliferation of bladder cancer cells by regulating the cancer cell cycle between the G1/S and G2/M phases (9).…”
Section: A B C Dsupporting
confidence: 87%
See 2 more Smart Citations
“…the 769-P and ACHN cells transfected with PLK1 siRNA demonstrated an increased percentage of cells in the G2/M phase, which supports the findings of previous studies (8,9). A previous study reported that PLK1 was important for the proliferation of bladder cancer cells by regulating the cancer cell cycle between the G1/S and G2/M phases (9).…”
Section: A B C Dsupporting
confidence: 87%
“…However, the possible heterogeneity of kidney tumors may make the identification of specific markers more challenging. A previous study revealed that PLK1 is overexpressed in renal cancer and participates in the proliferation and invasion of renal cancer cells (8). Although the evidence has elucidated the importance of PLK1 as a tumor promoter in renal cell carcinoma, the precise molecular mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we proved that NMS-P937 treatment significantly suppresses both clonogenic and migration ability of OS cells, which is highly relevant as it has been suggested that in other neoplasms PLK1 is involved in metastatic dissemination and malignancy [34][35][36].…”
Section: Discussionsupporting
confidence: 53%
“…In human somatic cells, inhibited Plk1 leads to multiple mitotic defects, including the formation of abnormal spindles, misaligned chromosomes and i mproper chromosom e condensation [10]. Additionally, up-or downregulation of Plk1 can induce a variety of human tumor cells or mouse embryonic cell mitotic defects, causing aneuploidy or cancer [11][12][13]. This study shows that Plk1 might play a critical role in the process of bipolar spindle assembly and chromosome arrangement during mitosis in somatic cells.…”
Section: Introductionmentioning
confidence: 74%